Precision of farmerbased fertility ratings and soil organic carbon for crop production on a Ferralsol - Musinguzi, P.; Ebanyat, Peter; Tenywa, J.S.; Basamba, T.A.A.; Tenywa, M.M.; Mubiru, D. (Copernicus GmbH, 2015)
Abstract. Simple and affordable soil fertility ratings are essential, particularly for the resource-constrained farmers in sub-Saharan Africa (SSA), in planning and implementing prudent interventions. A study was conducted on Ferralsols in Uganda to evaluate farmer-based soil fertility assessment techniques, hereafter referred to as farmers' field experiences (FFE), for ease of use and precision, against more formal scientific quantitative ratings using soil organic carbon (SQR-SOC). A total of 30 fields were investigated and rated using both techniques, as low, medium and high in terms of soil fertility – with maize as the test crop. Both soil fertility rating techniques were fairly precise in delineating soil fertility classes, though the FFE was inefficient in distinguishing fields > 1.2 % SOC with medium and high fertility. Soil organic carbon, silt and clay were exceptionally influential, accounting for the highest percentage in grain yield of 50 % in the topsoil (0–15 cm) and 67 % for the mean concentrations from 0 to 15 and 15 to 30 cm. Each unit increase in SOC concentration resulted in 966 to 1223 kg ha−1 yield gain. The FFE technique was effective in identifying low-fertility fields, and this was coherent with the fields categorized as low (SOC < 1.2 %). Beyond this level, its precision can be remarkably increased when supplemented with the SQR-SOC technique.